Perceptions, impacts and rewards of row planting of teff - Joachim Vandercasteelen; Mekdim Dereje; Bart Minten; Alemayehu Seyoum Taffesse (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2014)
This study analyzes the perceptions, impacts, and rewards of farmers who adopted row planting for the production of teff as a result of being exposed to a technology promotion campaign for row planting of teff in the Oromia region of Ethiopia. Our three main findings are as follows. First, despite a positive attitude towards row planting (and reduced seed rates in general) and a belief in the (large) yield increasing potential of row planting, exposed farmers only put a relatively small part of their plots aside for row planting in the next planting season. This indicates concerns with the additional labor requirement and possibly the need for more knowledge and experience with the new technology. Second, by implementing row planting, farmers experienced an increase in teff yield in the first year of implementation, but there was also a substantial increase in labor input requirements. A cost-benefit analysis shows that the increase in teff yield outweighs the cost of the extra labor in the first year of adoption when yields increase by 8 percent or more. Third, suitable mechanization for row planting would change the cost-benefit picture significantly and is shown to be an investment with possible high returns.
Keywords: 330; Ethiopia; teff yield; labor productivity; row planting; technology adoption; cost benefit